Coronary versus carotid blood flow and coronary perfusion pressure in a pig model of prolonged cardiac arrest treated by different modes of venoarterial ECMO and intraaortic balloon counterpulsation - Bělohlávek, Jan (BioMed Central, 2012)
INTRODUCTION: Extracorporeal membrane oxygenation (ECMO) is increasingly used in cardiac arrest (CA). Adequacy of carotid and coronary blood flows (CaBF, CoBF) and coronary perfusion pressure (CoPP) in ECMO treated CA is not well established. This study compares femoro-femoral (FF) to femoro-subclavian (FS) ECMO and intraaortic balloon counterpulsation (IABP) contribution based on CaBF, CoBF, CoPP, myocardial and brain oxygenation in experimental CA managed by ECMO. METHODS: In 11 female pigs (50.3 ± 3.4 kg), CA was randomly treated by FF versus FS ECMO ± IABP. Animals under general anesthesia had undergone 15 minutes of ventricular fibrillation (VF) with ECMO flow of 5 to 10 mL/kg/min simulating low-flow CA followed by continued VF with ECMO flow of 100 mL/kg/min. CaBF and CoBF were measured by a Doppler flow wire, cerebral and peripheral oxygenation by near infrared spectroscopy. CoPP, myocardial oxygen metabolism and resuscitability were determined. RESULTS: CaBF reached values > 80% of baseline in all regimens. CoBF > 80% was reached only by the FF ECMO, 90.0% (66.1, 98.6). Addition of IABP to FF ECMO decreased CoBF to 60.7% (55.1, 86.2) of baseline, P = 0.004. FS ECMO produced 70.0% (49.1, 113.2) of baseline CoBF, significantly lower than FF, P = 0.039. Addition of IABP to FS did not change the CoBF; however, it provided significantly higher flow, 76.7% (71.9, 111.2) of baseline, compared to FF + IABP, P = 0.026. Both brain and peripheral regional oxygen saturations decreased after induction of CA to 23% (15.0, 32.3) and 34% (23.5, 34.0), respectively, and normalized after ECMO institution. For brain saturations, all regimens reached values exceeding 80% of baseline, none of the comparisons between respective treatment approaches differed significantly. After a decline to 15 mmHg (9.5, 20.8) during CA, CoPP gradually rose with time to 68 mmHg (43.3, 84.0), P = 0 .003, with best recovery on FF ECMO. Resuscitability of the animals was high, both 5 and 60 minutes return of spontaneous circulation occured in eight animals (73%). CONCLUSIONS: In a pig model of CA, both FF and FS ECMO assure adequate brain perfusion and oxygenation. FF ECMO offers better CoBF than FS ECMO. Addition of IABP to FF ECMO worsens CoBF. FF ECMO, more than FS ECMO, increases CoPP over time.